2011
DOI: 10.1111/j.1865-1682.2011.01298.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of the West Nile Virus epidemic in Spain between 2010 and 2011

Abstract: West Nile virus (WNV) is a mosquito-transmitted flavivirus recognized as an emerging and re-emerging pathogen in different countries. This study describes the monitoring of the first WNV epidemic in Spain between 2010 and 2011. Between September and December 2010, 36 outbreaks of WNV in horses were reported in three different provinces of Andalusia (southern Spain), with no apparent spread outside this area. The temporal distribution and the clinical signs observed during the WNV epidemic in Spain were, in gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 40 publications
3
28
1
Order By: Relevance
“…Similar seroprevalences were also found in white-tailed deer in the United States [22, 23]. In contrast, a limited number of wild ruminants from south-western Spain tested during surveillance of WNV outbreaks were negative for flavivirus antibodies using the same bELISA [8]. In our study, no antibodies were detected in roe deer, potentially due to the small sample size, while a similar study in the Czech Republic reported flavivirus exposure in roe deer, mouflons, fallow deer and red deer [24].…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Similar seroprevalences were also found in white-tailed deer in the United States [22, 23]. In contrast, a limited number of wild ruminants from south-western Spain tested during surveillance of WNV outbreaks were negative for flavivirus antibodies using the same bELISA [8]. In our study, no antibodies were detected in roe deer, potentially due to the small sample size, while a similar study in the Czech Republic reported flavivirus exposure in roe deer, mouflons, fallow deer and red deer [24].…”
Section: Discussionmentioning
confidence: 55%
“…Five of them have circulated in Spain in the last decade. WNV exposure has been documented in mosquitoes [4], wild birds [5, 6] and different mammalian species, including humans [7], horses [8], dromedary camels ( Camelus dromedarios ) [9], wild boar ( Sus scrofa ) and Iberian pigs and red foxes ( Vulpes vulpes ) [10]. Clinical disease and mortality associated with WNV infection has also been detected in wild birds, horses and humans in this country [11, 12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monitoring of the first WNV epidemic in Spain (between 2010 and 2011) showed that many wetlands support large bird populations. The plenty of competent vectors indicate that ideal conditions for creating endemic cycles and WNV re-introduction are existed in Andalusia (Spain) [83]. …”
Section: Environmental Driversmentioning
confidence: 99%
“…The major WNF epidemic that occurred in 2010 in Central Macedonia, Greece, was caused by a lineage 2 strain [17,18]. Recently, human cases were reported from Albania, Hungary, Israel, Italy, Macedonia, the Palestinian territory, Romania, the Russian federation, Serbia, Spain, Ukraine, Tunisia, Turkey and Greece [12,19,20,21]. Most of the European countries have implemented surveillance networks, either passive of active, that have improved the quality of available epidemiological data.…”
Section: Introductionmentioning
confidence: 99%